Damage and yield loss estimate in maize varieties owing to stem borer (Chilo partellus Swinhoe) infestation and insecticidal control - Neupane, Saraswati; Subedi, Subash; Shrestha, Ramesh Kumar; Pandey, Sunita (Journal of Agriculture and Natural Resources, 2022)
Stem borer (Chilo partellus Swinhoe) is one of the most damaging and yield reducing pest in maize. Field experiments were organized to assess the extent of damage and yield loss due to the infestation of stem borer in maize following two factors randomized complete block design with three replications at National Maize Research Program, Rampur, Chitwan, Nepal, during two consecutive spring seasons of 2020 and 2021. Maize varieties; Rampur Hybrid (RH)-8, RH-10, RH-12 (CAH-1715), RH-14 (RML-86/RML-96), RH-16 (RML-95/RML-96), TX-369, Arun-2, ZM-401, ZM-627 and Rampur Composite were used as a test variety (First factor) whereas pest control conditions (spray and non-spray) was considered as the second factor in the experiments. The sprayed plots (protected plots) were kept completely free from stem borer infestation by using three application of standard dose of insecticide (spinosad 45% EC@0.4mL/L) at 10 days interval and non spray (unprotected plots) were selected for natural infestation of stem borers. Standard agronomical practices such as time of planting, row spacing, seed rate, irrigation, weeding and fertilizer application and doses were adopted to raise the crop. Among tested varieties Arun-2 was found most susceptible to stem borer attack in both experimental years resulted in higher % dead hearts (6.04%), higher no of exit hole (4.72), higher % foliage damage at before tasseling stage (12.17%) and higher tunnel length (4.62cm). Quantitative yield loss increased with the increase of the borer's infestation. The yield loss was ranged from 25 to 45% in different maize varieties due to the attack of stem borer. Highest yield loss was quantified for the open pollinated varieties, ZM-401(44.61%) followed by Rampur Composite (41.39%) and Arun-2 (41.22%). Spraying of insecticide enabled the recently introduced maize hybrid RH-14 to produce more yield and to be less vulnerable to stem borer damage.